PENGENALAN POLA SINYAL SEISMIK GUNUNG MERAPI DENGAN ALIHRAGAM GELOMBANG-SINGKAT - Novianta, Muhammad Andang (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Seismogram data from the monitoring representative the raw file in contain vario-us each information about circumstance perceived. The wavelet transform is methode can by us for indicating data and operator function in the different frequency element. Pattern recognition process seismic signal using wavelet transform have the higher level efficacy opportunity. By the wavelet enable time-frequency location. Thresholding method to limit and eliminate some part on the signal which are not important. By determining value of data parameter, the parts of limited the can be considered by a mixed noise.